Eating Smart and Moving More for Head Start: A Pilot Study - Virginia C. Stage; L. Suzanne Goodell; Susan Chase; Stephanie McDonald; Archana V. Hegde; Jocelyn Bayles; Lorelei Jones ([TEST] Journal of Extension, 2021)
Our study examined the relationship between improved personal health behaviors of Head Start teachers’ and the promotion of positive health behaviors in their classroom. Thirty-three Head Start teachers across 7 centers received six 30-minute nutrition education lessons. Dietary intake, physical activity, and self-efficacy for promoting positive health behaviors in the classroom were measured at baseline and post-intervention. Significant improvements were observed for dietary intake and physical activity. Self-efficacy for promoting health behaviors in the classroom did not significantly improve. Additional education is needed to improve health promotion practices. Lessons learned contributed to program refinement. Implications for Extension are discussed.
Keywords: Head Start; EFNEP; preschool; teachers; health behavior